2019
DOI: 10.2478/bjdm-2019-0015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of temporomandibular disorder in Turkish university students: A questionnaire study

Abstract: Summary Background/Aim: Temporomandibular dysfunction (TMD) might influence any individual with different signs and symptoms irrespective of gender or age. The aim of this study is to assess the prevalence of TMD in Oral and Dental Health Program students of İstanbul University-Cerrahpaşa. Material and Methods: This study include a sample of 486 students with age ranging from18 to 24 years. The presence and severity of TMD was evaluated using the Fonseca’s Anamnestic Index (FAI) and its questionnaire. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…5,11,12,16,31 Subclinical symptoms of TMD have been investigated with FAI, which is used in the early diagnosis and detection of TMD to prevent the progression and early treatment of TMD symptoms, enabling the rapid and accessible collection of large amounts of data at the minimum cost used in many previous studies. 5,19,32,33 Similar to previous studies conducted in various university student populations and reported TMD prevalence between 37-80% 5,[13][14][15][16][17]19,25 , this study, which included only dental assistant program students, also found a high prevalence of TMD (64.8%) compared to the prevalence of TMD absence (35.2%). These results may be due to differences in populations such as genetic structure, physiological differences, sex distribution, or social demographic characteristics, and the anxiety caused by the COVID-19 pandemic at the time of the study.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…5,11,12,16,31 Subclinical symptoms of TMD have been investigated with FAI, which is used in the early diagnosis and detection of TMD to prevent the progression and early treatment of TMD symptoms, enabling the rapid and accessible collection of large amounts of data at the minimum cost used in many previous studies. 5,19,32,33 Similar to previous studies conducted in various university student populations and reported TMD prevalence between 37-80% 5,[13][14][15][16][17]19,25 , this study, which included only dental assistant program students, also found a high prevalence of TMD (64.8%) compared to the prevalence of TMD absence (35.2%). These results may be due to differences in populations such as genetic structure, physiological differences, sex distribution, or social demographic characteristics, and the anxiety caused by the COVID-19 pandemic at the time of the study.…”
Section: Discussionsupporting
confidence: 85%
“…[11][12][13] Most of the epidemiological studies conducted on determining the prevalence of TMD have been conducted on university students studying any field related to health services. 1,3,5,[14][15][16][17] It has been reported that the prevalence of TMD shows a wide range between 47-81% in studies conducted on students from the Turkish population, with studies conducted in some of the populations. [15][16][17][18][19] TMD problems have been reported to be on the rise in the adolescent and adult population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The results are related to a study done in Brazil in 2018 which over two third of the adolescents had headache/ migraine and 36 percent of them connected it with TMD. 19 Though TMD is suggested to have a higher frequency and severity in females than in males, and females were reported to have a greater sensitivity to pain 20 which has been connected to hormonal, psychological, and even neurological changes, 8,9,21 no conclusive results achieved to the date. In this study TMD male patients (44.3%) were less than female patients (55.7%).…”
Section: Discussionmentioning
confidence: 99%
“…8 The results are related to a study done in Brazil in 2018 which over two third of the adolescents had headache/ migraine and 36 percent of them connected it with TMD. 18 Though TMD is suggested to have a higher frequency and severity in females than in males, and females were reported to have a greater sensitivity to pain 19 which has been connected to hormonal, psychological, and even neurological changes, 8,9,20 no conclusive results achieved to the date. In this study TMD male patients (44.3%) were less than female patients (55.7%).…”
Section: Discussionmentioning
confidence: 99%